Media Influence on the Academic Performance of Senior High School Students in Borongan City - Arago, Lorie Emmanuel B. (Future Science / FSH-PH Publications, 2025)
Social media are now the cornerstone in everyday life, with the rapid development of technologies shifting the way of communication and learning with different tools that influence student learning in education. The study investigates the media's influence on the academic performance of senior high school students. A total of 325 Grade 11 students were chosen through stratified random sampling, and those selected respondents were senior high school students of the Schools Division of Borongan City. The descriptive-correlational research design and an adopted structured research questionnaire were utilized. Results revealed that Facebook had the highest usage among senior high school students for academic and social purposes. TikTok, Messenger, YouTube, and Instagram are following it. The social media platforms greatly influence the students' academic performance through communication, social skills, and time management. Furthermore, time management had an average score on social media, which indicates that students need to balance life using gadgets and education outcomes. On the distribution of respondents in terms of academic performance, results show that most of the respondents belong to the Outstanding level (60.3%), followed by the Very Satisfactory level (33.5%) and Satisfactory level (6.2%). Testing the relationship between the influence of social media and the academic performance of senior high school students reveals significant correlations that highlight the multifaceted role social media plays in education. The study recommends the limitations of using Facebook and other social media platforms, especially for struggling learners in academic performance in schools. Schools initiate programs, projects, and activities related to anti-cyberbullying, the Internet Safety Act, and Cybercrime Prevention Seminars for the students. Provide peer tutoring and give insights on how to be responsible online users. Benchmarking to improve academic performance using social media platforms and school authorities manage, support, and innovate using social media education.